Latina/o Hope - Diaz Soto, Lourdes; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
There are an estimated forty-eight million Latinas/os living in the United States, roughly sixteen percent of the population. Not only are they the largest minority group in the country but also the youngest: one out of five children is Latina/o. The rise in the Latina/o population has caused for panic in some areas of the country, resulting in hostile and sometimes violent racism and xenophobia, and yet, much of that hatred is fueled not on facts but rather on myths about immigration. To date, most studies on immigration have been data driven, focusing on migrating groups or policy analyses. Latina/o Hope is different. It incorporates salient theories on migration as it moves toward a new theorizing, one that views immigration from the immigrant's perspective. Thus, it integrates research into the depiction of various slices of immigrant experience$1 (Bthe young women disappearing in the city of Juarez, the various students at various stages of their educational journeys, the young children in need of ESL programs, the ethnically-mixed immigrants, the undocumented workers, and others. Latina/o Hope discusses the impact of neoliberal policies and global capitalization on the daily lives of Latina/o immigrants, serving as an inspiration for dialogue, praxis and imagination to love and serve one another.s
Keywords: Education; Education; Sociology of Education; International and Comparative Education